2011
DOI: 10.12693/aphyspola.120.63
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Structural and Optical Properties of GDC Thin Films Deposited by Reactive Magnetron Sputtering

Abstract: The purpose of this paper was to analyze structural and optical properties of gadolinia-doped ceria (GDC, Ce0.9Gd0.1O1.95) thin films. At first the ceria-gadolinia multilayer sandwich systems (4-12 layers) were deposited using reactive magnetron sputtering in the O2/Ar gas mixtures. The films were formed with ≈ 90% ceria and ≈ 10% gadolinia. The GDC thin films deposited on Si (111) substrate were annealed at 600• C for 1 h in air. The thickness of the formed GDC multilayer systems was about 600 nm. The GDC thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…In the works reported on the sputter deposition of GDC, only few papers report information about the crystalline orientation of the deposited films. Most of them indicate a random orientation [3,4,11,12,14,[17][18][19][20][21]29,46] and only a few report a preferential [111] orientation [10,13,26,30,34]. The change from random to [111] orientation for the films deposited at the shortest distance in our work is in agreement with these works.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the works reported on the sputter deposition of GDC, only few papers report information about the crystalline orientation of the deposited films. Most of them indicate a random orientation [3,4,11,12,14,[17][18][19][20][21]29,46] and only a few report a preferential [111] orientation [10,13,26,30,34]. The change from random to [111] orientation for the films deposited at the shortest distance in our work is in agreement with these works.…”
Section: Discussionsupporting
confidence: 91%
“…Among these techniques, magnetron sputtering offers the advantage of easy scalability to industrial processes. There are several reports of the deposition of GDC films using both radio frequency (RF) [10][11][12][13][14][15][16][17][18][19] and direct current (DC) [4,7,[20][21][22][23][24][25][26][27][28][29][30][31][32] magnetron sputtering, as well as high power impulse magnetron sputtering (HiPIMS) [33,34]. The different methods have each their own advantages and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with the exception of the film from methanol at 400 °C, the films were found to be insoluble in acid (HNO 3 , 0.25 M) and base (KOH, 0.60 M). From texture coefficient calculations, all crystalline films showed a preferred orientation along the (200) plane. Furthermore, it was found that the (200) diffraction peak became more dominant with increasing temperature when films were deposited using methanol.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, under the present experimental condition of sputtered nickel oxide films, the crystallites preferred to grow on plane (101). The texture coefficient T c (hkl) examined the preferred growth/orientation according to the following equation [24,25]:…”
Section: Surface Morphology Investigationmentioning
confidence: 99%